Application of Evidence-Based Nursing Practice Benson Relaxation in Cancer Patients Undergoing Chemotherapy to Reduce Nausea and Improve Sleep Quality: Case Report: Penerapan Evidence – Based Nursing Practice Relaksasi Benson Pada Pasien Kanker Yang Menjalani Kemoterapi Terhadap Penurunan Mual Dan Peningkatan Kualitas Tidur: Case Report - Ikhtiarani, Inggil; Aprianti, Tutty (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Nasopharyngeal cancer is a type of malignancy that is common found cancer in Indonesia. One of the medical treatments for cancer is chemotherapy, the effects occur decreased sleep quality. An intervention reduce nausea and improve sleep quality in chemotherapy patients is Benson relaxation. This research aims to apply Evidence Based Nursing Practice Benson's relaxation to reduce nausea and improve sleep quality in cancer patients using